Circulating miсroRNAs in patients with ischemic heart disease with type 2 diabetes mellitus - Serik, S. A.; Serdobinska-Kanivets, E. M.; Bondar, T. M. (Pathologia, 2020)
The aim of the study was to investigate circulating miRNAs-27a, -221 levels and their relationship with glycemia and insulin resistance in patients with ischemic heart disease (IHD) with type 2 diabetes mellitus. Materials and methods. The study included 58 patients with stable IHD with type 2 diabetes and 22 patients with IHD without diabetes. The control group consisted of 19 healthy persons. MicroRNAs-27a and -221 were determined in blood plasma by real time polymerase chain reaction. Small nuclear RNA U6 was used as endogenous control. Results. In patients with IHD with diabetes circulating microRNAs27a and -221 levels were lower than in the controls (P = 0.024, P = 0.006, respectively) and in nondiabetic patients with IHD (P = 0.011, P = 0.001, respectively). In nondiabetic patients with IHD microRNAs-27a and 221 levels were nonsignificantly higher than in the controls (P > 0.05, for both). In diabetic patients with IHD the positive correlation between microRNAs (R = 0.319, P = 0.027) was significantly weaker than in the controls (R = 0.889, P < 0.001) (P < 0.001) and in nondiabetic patients with IHD (R = 0.772, P < 0.001) (P = 0.020). In patients with IHD with diabetes microRNA-27a negatively correlated with glycosylated hemoglobin (R = -0.339, P = 0.030), and microRNA-221 negatively correlated with the HOMA-IR (R = -0.362, P = 0.006). According to the ROC-analysis the decrease of both miRNAs levels was significantly associated with the presence of diabetes in patients with IHD. AUC for microRNA-27a was 0.692 (CI: 0.575–0.793, P = 0.009), AUC for microRNA-221 was 0.728 (CI: 0.617–0.821, P = 0.001). Conclusions. In patients with IHD with type 2 diabetes mellitus circulating microRNAs-27a and -221 levels significantly decreased in comparison with both control and patients with IHD without diabetes. The decrease of microRNA-27a was associated with hyperglycemia, and the decrease of microRNA-221 was associated with the increase of insulin resistance. In patients with IHD without diabetes these microRNAs levels did not change.